Flood and Landslide Natural Disasters and Its People Prevention Effort - Murdiyanto, Murdiyanto; Gutomo, Tri (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research is meant to know the condition of flood and landslide and its people prevention effort. This research took place in Jayapura Municipality based on the consideration that in that place flood and landslide disasters happend very often. Data were gathered through opened interview, observation, and documentary analysis, then analysied through qualitative-descriptive technique. The research showed that Jayapura municipality condition are mostly mountainous, highland, and fyords, prone to flood and landslide natural disastesr. Natural disasters in Jayapura were caused by cutting down forest trees, shalowing river bed, and narrowing river width. The effort that has been done by locals are through informing and awareness to local people on the benefit of planting and the impact of rubbish littering, river bed dredging, widening river, and banning to build house on river sides. Landslide was caused by land occupying on water conservation, deforestation and worse city plan. The prevention effort is to refunction water conservation area, awaring locals on the benefit of environmental greening, and repairing better city plan, and prohibition making houses on the slope, and drainage betterment. Based on the research can be concluded that Jayapura city is an area prone to natural disaster, especially flood and landslide. The effort to prevent is needed, with the participation of local government, social organization, public figures, local people, and families, both on forestry management, keeping current river swift, drainage, keeping conservation area, and a better city zoning.